Petracomline Strategy in Entrepreneurial Soft Skills in Students of the IESTP "Andrés Avelino Cáceres Dorregaray", Huancayo - Salcedo Núñez, Mariella (2022)
In the investigation, it was contrasted to hypothesize "The application of the PETRACOMLINE strategy significantly improves the level of knowledge of the entrepreneurial soft skills of two students of a Public Technological Higher Education Institute of the Junín region". It was investigated with a quantitative approach and with a quasi-experimental design, in a sample of 60 students. Six sessions were held, with six extracurricular tasks, to develop six skills, applying a test to measure or knowledge about soft skills at the end of the experiment, obtaining as a result that the experimental group presented a better level of knowledge than the control group.